2009
DOI: 10.2119/molmed.2008.00105
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Cholinergic Antiinflammatory Pathway Reduces Ricin-Induced Mortality and Organ Failure in Mice

Abstract: Exposure to ricin, either by accident through ingestion of castor oil plant seeds or intentionally through its use as a bioweapon, invariably leads to multiple organ damage and death. Currently there is only a vaccine in advanced development to ricin, but no other antidote. Ricin causes systemic inflammation with increased proinflammatory cytokine release and subsequent multiple organ failure, particularly kidney and liver dysfunction. Activation of the cholinergic antiinflammatory pathway, specifically throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…In AD, the cholinergic system is downregulated [1]; thus, inflammatory processes in both the central nervous system and peripheral tissues may be caused by downregulation of ACh [3]. NMDAR expression is also upregulated in central nervous system disorders, leading to hyperactivity of the inflammatory system [4].…”
Section: Introductionmentioning
confidence: 99%
“…In AD, the cholinergic system is downregulated [1]; thus, inflammatory processes in both the central nervous system and peripheral tissues may be caused by downregulation of ACh [3]. NMDAR expression is also upregulated in central nervous system disorders, leading to hyperactivity of the inflammatory system [4].…”
Section: Introductionmentioning
confidence: 99%
“…Mabley et al (2009) also showed that organ damage including kidney and liver failure could be diminished by activation of the cholinergic anti-inflammatory pathway using nicotine administration in mice (14). They showed that this management could delay mortality and increase survival rate (14). However, no certain antidote has been suggested to treat the patients.…”
Section: Discussionmentioning
confidence: 99%
“…pChE). Moreover, downregulation of acetylcholine (ACh) causes inflammatory hyperactivation of the CNS and peripheral nervous system [9,10]. Therefore, we speculated that this inflammatory hyperactivation appeared simultaneously in both systems.…”
Section: A Pche As a Biomarker In Admentioning
confidence: 99%
“…Because ACh can suppress inflammation in both CNS and peripheral tissues [9,10], pChE hyperactivity also induces inflammatory hyperactivation via ACh downregulation. Therefore, pChE hyperactivation is not favorable in conditions such as AD, DM and LMD where inflammatory hyperactivation may be considered causative [11].…”
Section: A Pche As a Biomarker In Admentioning
confidence: 99%